High-speed 4 × 4 silicon photonic plasma dispersive switch, operating at the 2 µm waveband - Wang, Jiawei (2024)
The escalating need for expansive data bandwidth, and the resulting capacity constraints of the single mode fiber (SMF) have positioned the 2-μm waveband as a prospective window for emerging applications in optical communication. This has initiated an ecosystem of silicon photonic components in the region driven by CMOS compatibility, low cost, high efficiency and potential for large-scale integration. In this study, we demonstrate a plasma dispersive 4 × 4 photonic switch operating at the 2-μm waveband with the highest switching speed. The demonstrated switch operates across a 45-nm bandwidth, with 10-90% rise and 90-10% fall time of 1.78 ns and 3.02 ns respectively. In a 4 × 4 implementation, crosstalk below -15 dB and power consumption lower than 19.15 mW across all 16 optical paths are indicated. This result brings high-speed optical switching to the portfolio of devices at the promising waveband.